Utilization of Red Brick Demolition Waste as a Substitute for Fine Aggregate in Paving Block Mortar - Raja Riono; Sunarno Sunarno; Anis Aulia Ulfa (Nusantara Civil Engineering Journal, 2026)
Paving blocks are construction materials composed of cement, fine aggregate, and water. Continuous use of natural fine aggregates may increase environmental exploitation; therefore, environmentally friendly alternative materials are needed, one of which is red brick demolition waste. This study aimed to determine the effect of red brick waste substitution as fine aggregate on the compressive strength of paving block mortar. The substitution variations used were 0%, 5%, 10%, 15%, and 20% of the fine aggregate weight. Cube specimens measuring 5 cm × 5 cm × 5 cm were prepared with three samples for each variation. Compressive strength tests were conducted at the ages of 7 and 14 days. The results showed that the highest compressive strength was obtained in the normal mixture (0%) with values of 142.75 kg/cm² at 7 days and 183.54 kg/cm² at 14 days. The addition of red brick waste reduced the compressive strength at the 5% variation, but the strength gradually increased up to the 20% variation. The 20% variation produced compressive strengths of 126.44 kg/cm² at 7 days and 127.80 kg/cm² at 14 days. Based on these results, red brick waste has the potential to be used as a partial substitute for fine aggregate in paving block mortar.